68Ga-DOTA-FAPI-04 PET/CT as a Promising Tool for Differentiating Ovarian Physiological Uptake: Preliminary Experience of Comparative Analysis With 18F-FDG - Wang, Qixin; Yang, Songsong; Tang, Wenxin; Liu, Lin; Chen, Yue (Frontiers in Medicine, 2021)
Objectives: This study aimed to investigate the physiological distribution characteristics of 68Ga-DOTA-FAPI-04 in the ovary, and assess the feasibility of early diagnosis of primary ovarian disease with 68Ga-DOTA-FAPI-04 PET/CT. Methods: We retrospectively analyzed the data of patients who received 18F-FDG and 68Ga-DOTA-FAPI-04 PET/CT scanning in the Nuclear Medicine Department of our hospital within 3 days from September 2020 to January 2021. We selected the data in which ovaries showed abnormal FDG activity. Patients with abnormal ovarian FDG uptake with focus confirmed by pathological biopsy or clinical follow-up as pathological changes were excluded. The uptake of tracers (18F-FDG and 68Ga-FAPI) was semi-quantitatively analyzed. Results: This study included 14 patients (average age was 38.6). Physiological ovarian uptake was mostly unilateral, and there was no significant difference in SUVmax between the left and right sides (FDGt = 0.272, FAPIt = 0.592). The ovary SUVmax of FDG (4.89 ± 1.84) was statistically significantly higher than that of FAPI (1.53 ± 0.37). The Le/Li ratio on FDG is 3.38 ± 1.81, TBR is 5.81 ± 1.98, while the Le/Li ratio on FAPI is 3.57 ± 1.26, TBR is 0.94 ± 0.19. Conclusion: Our research shows that ovarian functional or pathological changes can be manifested as FDG avid, while 68Ga-DOTA-FAPI-04 has no physiological accumulation in the ovary and is not affected by the menstrual cycle. Therefore, 68Ga-DOTA-FAPI-04 has unique advantages in the diagnosis of ovarian diseases, and can identify them early and accurately.